Water-based adhesive and its manufacturing method and application
By designing a water-based adhesive composed of polymeric metal salts and polymerizable units, the existing adhesive is solved to solve the problem of bonding, charging and discharging and cycling performance between the lithium-ion battery pole and the battery, and the efficient, reliable and environmentally friendly production of the battery is achieved.
Patent Information
- Application Number
- JP2024556335
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-19
- Filing Date
- 2022-12-21
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-12-21
AI Technical Summary
In the application of existing water-based adhesives in high-performance lithium-ion battery poles and batteries, it is difficult to meet good bonding performance, fast charging and discharge performance and cycling performance at the same time.
A water-based adhesive consisting of polymeric metal salts and polymerizable units is designed, which includes a polymerizable unit composed of acrylate units and halocarbon units, and a polymeric metal salt consisting of metal phosphate, carboxylic polymer, metal sulfate or disulfamide polymer. By adjusting the ratio of polymeric metal salts and polymerizable units, an adhesive with suitable expansion properties, excellent adhesive properties and lithium ion conductivity is prepared.
This water-based adhesive significantly improves circulation and fast charging performance in battery pole and lithium-ion batteries, ensuring high efficiency and reliability of the battery while reducing production costs and environmental impact.
Smart Images

Figure 2025511584000001 
Figure 2025511584000002 
Figure 2025511584000003
Abstract
Description
[Technical field]
[0001] The present application relates to the field of lithium ion battery material technology, such as water-based adhesives and their manufacturing methods and applications. [Background technology]
[0002] In recent years, in order to meet the demand for electrified equipment, especially the further development of the mobile phone and electric vehicle industries, the performance improvement of lithium-ion batteries is also facing great challenges. At present, not only is the market need for higher energy density of lithium-ion batteries, but the functional requirements for fast charging are also becoming more and more important. Adhesives are one of the main components of battery pole pieces, and are used to connect active materials, conductive agents and electrode current collectors and ensure the overall connection between them. In the charging and discharging process, adhesives effectively maintain the integrity of the electrode structure and ensure that the electrode material can repeatedly insert and remove lithium, and also play an important role in maintaining cycle performance. Adhesives have an important impact on the electrical performance of pole pieces and batteries, and high-performance lithium-ion batteries require high-performance adhesives to match them.
[0003] Polyvinylidene fluoride (PVDF) is currently the most common oil-based adhesive in lithium-ion batteries. It has excellent redox ability and stability, but needs N-methylpyrrolidone (NMP) as the solvent to achieve good dispersion. NMP has a high volatility temperature, is expensive, is unfavorable to human health, and has the risk of environmental pollution. In addition, PVDF is easily hydrolyzed, so the environmental humidity needs to be strictly controlled in the production process of the pole pieces, which increases the production cost of the battery, and PVDF swells in the electrolyte, affecting the reliability and safety of the battery.
[0004] Replacing oil-based adhesives such as PVDF with water-based adhesives to make the lithium battery manufacturing process environmentally friendly is currently one of the development trends of battery pole pieces. At present, existing water-based adhesives include polyacrylic acid (PAA), sodium carboxymethyl cellulose / styrene butadiene rubber (CMC / SBR), sodium alginate, chitosan, etc., among which, SBR-type adhesives are widely used in negative electrode systems because of their low addition amount to the system and strong adhesive strength between the active material and the current collector, but the polarity of the components in the SBR adhesive is low, and the affinity with the strong polar electrolyte is low, and the dynamic performance of the lithium-ion battery as an adhesive is low, so it cannot achieve satisfactory fast charging performance. In addition, SBR is generally used in combination with CMC, which is a thickener, and the adhesive performance of CMC is ordinary, and it is very brittle, making it easy for the pole pieces to crack during charging and discharging. CN109802139A discloses an aqueous adhesive and a battery, which includes an adhesive component containing one of styrene butadiene latex and polyacrylic acid, and a thickening component containing one of cyclodextrin and chitosan. The aqueous adhesive can effectively reduce the shuttle effect of the intermediate product, reduce the risk of peeling, and improve the electrochemical performance of the battery. However, the glass transition temperature of polyacrylic acid is relatively high and relatively hard at room temperature, and the pole pieces are prone to become hard and brittle. Therefore, the PAA aqueous adhesive has defects such as cracking during the application process and stripes appearing after cold rolling, and there is a phenomenon of powder scattering at the curved part of the pole pieces during the winding process, which limits its versatility in batteries. In addition, natural polymer materials such as sodium alginate and chitosan are excellent as adhesives in terms of environmental friendliness and water solubility, but have many shortcomings in electrochemical performance, mechanical performance, adhesive performance, etc., making it difficult to meet the application requirements of batteries.
[0005] Therefore, developing a water-based adhesive material that simultaneously has excellent adhesive performance, rate performance and cycle performance to meet the application requirements of high-performance battery pole pieces and lithium-ion batteries is a problem to be solved in the field. Summary of the Invention
[0006] The following is a summary of the subject matter described in detail herein, which is not intended to limit the scope of the claims.
[0007] The present application provides an aqueous adhesive and its manufacturing method and application. By designing structural units such as polymer metal salt and polymerizable monomer, the aqueous adhesive has excellent adhesive performance, lithium ion conductivity and suitable swelling properties, and can be used in battery pole pieces and lithium ion batteries to significantly improve the cycle performance and rate performance of the battery.
[0008] According to a first aspect, an embodiment of the present application provides an aqueous adhesive, the aqueous adhesive being a copolymer formed by a polymeric metal salt and a polymerizable monomer, the polymerizable monomer including a combination of an acrylate-based monomer and an olefin-based monomer, and the polymeric metal salt being any one or a combination of at least two selected from a metal phosphate-based polymer, a metal carboxylate-based polymer, a metal sulfonate-based polymer, and a metal bissulfonylimide-based polymer.
[0009] The aqueous adhesive provided by the present application is a copolymer formed by the reaction of a polymer metal salt and a polymerizable monomer, the polymerizable monomer includes a combination of an acrylate monomer and an olefin monomer having different solubility parameters, and a copolymer segment formed by designing structural units such as a specific type of polymer metal salt, polymerizable monomer, etc., includes a specific repeating structural unit to obtain a product with different solubility parameters, and the aqueous adhesive has suitable swelling properties, and at the same time, the structural fragments of the polymer metal salt can increase the strength of the adhesive and the content of the metal salt, thereby providing the aqueous adhesive with excellent adhesive performance and lithium ion conductivity. The aqueous adhesive provided by the present application has a good balance effect between adhesive performance, lithium ion conductivity, and swelling properties by designing the structural units in the copolymer, and has excellent adhesive strength, adhesive stability, and electrochemical performance at the same time, thereby significantly improving the cycle performance and rate performance of the battery pole piece and lithium ion battery containing it.
[0010] Preferably, the polymeric metal salt comprises any one or a combination of at least two of a polymeric lithium salt, a polymeric sodium salt, a polymeric potassium salt, or a polymeric magnesium salt.
[0011] Preferably, the metal phosphate polymer is any one or a combination of at least two selected from metal polyphosphate, 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate metal salt-based polymer, bis(2-(methacryloyloxy)ethyl)phosphate metal salt-based polymer, 2-methacryloyloxyethyl phosphate metal salt-based polymer, and vinyl metal phosphate metal salt-based polymer, and more preferably any one or a combination of at least two selected from lithium polyphosphate, 2-methyl-2-acrylic acid-2-hydroxyethyl ester lithium phosphate lithium polymer, bis(2-(methacryloyloxy)ethyl)phosphate lithium polymer, 2-methacryloyloxyethyl lithium phosphate polymer, and vinyl lithium phosphate polymer.
[0012] Preferably, the above-mentioned carboxy metal salt-based polymer is any one or a combination of at least two selected from a metal methacrylate-based polymer, a metal acrylate-based polymer, a metal maleate-based polymer, a metal itaconate-based polymer, a metal triallyl citrate-based polymer, a metal carboxymethylcellulose-based polymer, or a metal alginate-based polymer, and more preferably any one or a combination of at least two selected from a lithium methacrylate-based polymer, a lithium acrylate-based polymer, a lithium maleate-based polymer, a lithium itaconate-based polymer, a lithium triallyl citrate-based polymer, a lithium carboxymethylcellulose-based polymer, or a lithium alginate-based polymer.
[0013] Preferably, the sulfonic acid metal salt polymer is any one or a combination of at least two selected from styrene sulfonic acid metal salt polymers, vinyl sulfonic acid metal salt polymers, propenyl sulfonic acid metal salt polymers, methacrylic acid metal salt polymers, 4-vinylbenzenesulfinic acid metal salt polymers, allyl vinyl sulfonic acid metal salt polymers, 3-sulfopropyl methacrylic acid metal salt polymers, methacrylic acid 2-ethanesulfonate metal salt polymers, 2-acrylamido-2-methyl-1-propanesulfonic acid metal salt polymers, acrylic acid-2-acrylamido-2-methylpropanesulfonic acid metal salt polymers, and 3-allyloxy-2-hydroxy-1-propanesulfonic acid metal salt polymers, and more preferably, styrene sulfonic acid metal salt polymers. The polymerizable compound is any one or a combination of at least two selected from the group consisting of lithium-based polymers, sodium styrenesulfonate-based polymers, potassium styrenesulfonate-based polymers, lithium vinylsulfonate-based polymers, lithium propenylsulfonate-based polymers, lithium methacrylic acid sulfonate-based polymers, lithium 4-vinylbenzenesulfinate-based polymers, lithium allylvinylsulfonate-based polymers, 3-sulfopropyl methacrylate-based polymers, methacrylic acid 2-ethanesulfonate lithium-based polymers, 2-acrylamido-2-methyl-1-propanesulfonate-based polymers, acrylic acid-2-acrylamido-2-methylpropanesulfonate-based polymers, and 3-allyloxy-2-hydroxy-1-propanesulfonate-based polymers.
[0014] Preferably, the above-mentioned bissulfonylimide metal salt-based polymer is selected from vinyl bissulfonylimide metal salt-based polymers and / or styrene bissulfonylimide metal salt-based polymers, and more preferably, vinyl bissulfonylimide lithium-based polymers and / or styrene bissulfonylimide lithium-based polymers.
[0015] In this application, the "polymer" in the above polymer metal salt includes homopolymer and / or copolymer, and taking "metal methacrylate-based polymer" as an example, as long as the polymer contains a structural unit consisting of metal methacrylate, the polymer may be a homopolymer of metal methacrylate or a copolymer of metal methacrylate and other monomers. Other polymers have the same meaning, and for the sake of brevity, the description thereof is omitted.
[0016] Preferably, the weight average molecular weight of the polymer metal salt is 1000 to 10,000,000, such as 2,000, 5,000, 8,000, 10,000, 30,000, 50,000, 80,000, 100,000, 300,000, 500,000, 800,000, 100,000, 3,000,000, 5,000,000, 7,000,000, or 9,000,000, and specific point values therebetween, but limited by space and brevity, the present application does not exhaustively recite specific point values within the above ranges.
[0017] In the present application, the polymer metal salt can be purchased from the market, or can be obtained by subjecting an acidic polymer to a metal salt-forming treatment by a method known in the prior art.
[0018] Preferably, when the total mass of the polymer metal salt and the polymerizable monomer is 100%, the mass of the polymer metal salt is 1 to 90%, for example, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, and specific point values between the above point values, limited for reasons of space and brevity, the present application does not exhaustively recite specific point values included in the above range, but more preferably, 10 to 50%.
[0019] In the preferred technical solution of the present application, the mass ratio of the polymer metal salt is 1-90%, more preferably 10-50%, so that the copolymer formed by the reaction contains structural fragments of the polymer metal salt in an appropriate ratio, which gives the aqueous adhesive excellent adhesion performance and lithium ion conductivity, and at the same time, shows appropriate swelling properties, so that the lithium ion battery containing the aqueous adhesive has even better cycle performance and rate performance. If the mass ratio of the polymer metal salt is too low, the strength of the aqueous adhesive decreases, and at the same time, the swelling rate in the electrolyte increases, so that the adhesive strength is severely attenuated after long-term use, resulting in poor cycle performance of the battery. If the mass ratio of the polymer metal salt is too high, the flexibility of the aqueous adhesive is insufficient, which affects the processing performance of the pole pieces.
[0020] Preferably, the acrylate monomer is an alkyl acrylate and / or an alkyl methacrylate. Preferably, the "alkyl group" in the above alkyl acrylate and alkyl methacrylate is independently a C1 to C10 linear or branched alkyl group, for example, a C1, C2, C3, C4, C5, C6, C7, C8, C9 or C10 linear or branched alkyl group. For example, when the alkyl group is C1, it represents methyl acrylate or methyl methacrylate, and by analogy therewith, explanation thereof will be omitted for the sake of brevity.
[0021] Preferably, the acrylate monomer includes any one or a combination of at least two of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, pentyl acrylate, pentyl methacrylate, hexyl acrylate, hexyl methacrylate, octyl acrylate, isooctyl acrylate, or octyl methacrylate.
[0022] Preferably, the olefinic monomer includes any one or a combination of at least two of styrene, C5 to C10 (eg, C5, C6, C7, C8, C9 or C10) linear or branched chain olefins. Preferably, the C5 to C10 (e.g., C5, C6, C7, C8, C9 or C10) linear or branched olefins include, but are not limited to, pentene, hexene, heptene, octene, nonene, decene, and the like, and each isomer of the above olefins.
[0023] Preferably, the mass ratio of the acrylate monomer to the olefin monomer is (0.5 to 2):1, and may be, for example, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, or 1.9:1, and is more preferably (0.8 to 1.5):1.
[0024] In the preferred technical solution of the present application, the mass ratio of the acrylate monomer to the olefin monomer is (0.5-2):1, more preferably (0.8-1.5):1, and the copolymer formed by the reaction contains a specific ratio of polyacrylate structural fragments and polyolefin structural fragments, so that the aqueous adhesive has suitable swelling properties, excellent adhesive performance and lithium ion conductive ability, and the ratio of two polymerizable monomers with different solubility parameters is controlled to obtain a product with different solubility parameters, so that the swelling performance of the aqueous adhesive in the electrolyte can be adjusted, and the swelling degree is not too high to lose adhesive strength, or too low to lose lithium ion conductive ability. If the amount of the acrylate monomer used is too large, the swelling degree of the aqueous adhesive in the electrolyte will be high, and the adhesive strength will be attenuated after long-term use, resulting in poor cycle performance of the battery. If the amount of the olefin monomer used is too large, the swelling degree of the aqueous adhesive will be low, and the lithium ion conductive ability cannot be well exerted, which will affect the rate performance of the battery pole piece and the lithium ion battery.
[0025] Preferably, the polymerizable monomer further includes a functional monomer. Preferably, the functional monomer comprises acrylic acid and / or methacrylic acid. Preferably, the mass percentage content of the functional monomer in the polymerizable monomer is ≦10%, and may be, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 9.5%.
[0026] As a preferred technical solution of the present application, the polymerizable monomer further comprises a functional monomer that contributes to the emulsion stability of the water-based adhesive.
[0027] According to a second aspect, an embodiment of the present application provides a method for producing the water-based adhesive according to the first aspect, the method comprising mixing a polymeric metal salt, a polymerizable monomer, an initiator and a solvent, followed by reacting to obtain the water-based adhesive.
[0028] Preferably, the initiator comprises a persulfate, more preferably ammonium persulfate. Preferably, when the mass of the polymerizable monomer is taken as 100%, the mass of the initiator is 0.05-5%, for example, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%, and specific point values between the above point values, and limited by space and brevity, the present application does not exhaustively recite specific point values included in the above range.
[0029] Preferably, the solvent comprises water.
[0030] Preferably, the temperature of the reaction is 60-80°C, for example, 61°C, 63°C, 65°C, 68°C, 70°C, 71°C, 73°C, 75°C, 77°C or 79°C, and specific point values between the above point values, and limited by space and brevity, the present application does not exhaustively recite specific point values included in the above range.
[0031] Preferably, the reaction time is 1-12 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or 11 h, and may be specific point values between the above point values, and limited by space and brevity, the present application does not exhaustively recite specific point values within the above range.
[0032] Preferably, the method further comprises a neutralization step after completion of the reaction. Preferably, the neutralizing agent is a lithium hydroxide solution.
[0033] According to a third aspect, the present application provides an application of the water-based adhesive according to the first aspect in battery materials. Preferably, the battery material is a lithium ion battery material.
[0034] According to a fourth aspect, embodiments of the present application provide a battery pole piece comprising the water-based adhesive according to the first aspect. Preferably, the battery pole piece includes a current collector and a coating layer disposed on the current collector, and the material of the coating layer includes the water-based adhesive described in the first embodiment.
[0035] Preferably, the material of the coating layer includes an active material, a conductive agent, and the water-based adhesive according to the first embodiment.
[0036] Preferably, the battery pole piece is a negative pole piece.
[0037] According to a fifth aspect, an embodiment of the present application provides a lithium ion battery comprising the water-based adhesive according to the first aspect and at least one of the battery pole pieces according to the fourth aspect.
[0038] The embodiments of the present application have the following beneficial effects over the related art. In the aqueous adhesive provided by the embodiment of the present application, the copolymer segment formed contains a specific repeating structural unit through the design of structural units such as polymer metal salt and polymerizable monomer and their synergistic action, so that the aqueous adhesive has suitable swelling properties, excellent adhesive performance and lithium ion conductivity, and its swelling rate in the electrolyte (85°C, 24h) can be adjusted within the range of 10-100%, peel stress is 15-30N / m, and it has excellent adhesive strength, adhesive stability and electrochemical performance at the same time, and the cycle performance and rate performance of the lithium ion battery containing it are significantly improved. When the aqueous adhesive is used for the negative electrode piece, the lithium ion battery has a capacity retention rate of ≥98% at 100 cycles at room temperature, a 3C capacity retention rate of ≥94%, and excellent cycle performance and rate performance, which can meet the application requirements of high-performance lithium ion batteries.
[0039] Other aspects will become apparent upon reading and understanding of the drawings and detailed description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The technical solutions of the present application are further described below through specific embodiments. Those skilled in the art should understand that the above examples are only for aiding the understanding of the present application, and do not specifically limit the present application. As used herein, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, product, or apparatus that comprises recited elements is not necessarily limited to those elements, but may further include other elements not expressly recited or elements inherent to such composition, step, method, product, or apparatus.
[0041] "Optionally" or "any one" means that the subsequently described item or event may or may not occur, and the statement includes cases where the event occurs and cases where it does not occur. The indefinite articles "a" and "one" before an element or component herein do not limit the numerical requirement (i.e., the number of occurrences) of the element or component. Thus, "a" or "one" should be interpreted as including one or at least one, and the singular element or component also includes the plural, unless the said number clearly refers to the singular only.
[0042] The use of terms such as "one embodiment," "some embodiments," "illustratively," "particular examples," or "some examples" in this application means that the particular feature, structure, material, or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of this application. Exemplary uses of the terms in this specification do not necessarily refer to the same embodiment or example.
[0043] Furthermore, the technical features of each embodiment of the present application can be combined with each other as long as they are not inconsistent with each other.
[0044] Example 1 An aqueous adhesive and its manufacturing method, the aqueous adhesive is a copolymer formed by reacting lithium polyacrylate (weight average molecular weight is 10000, purchased from Macklin) with a polymerizable monomer, the mass ratio of the lithium polyacrylate to the polymerizable monomer is 1:2, the polymerizable monomer is a mixed monomer of styrene (St), butyl acrylate (BA) and acrylic acid (AA), and contains 50% styrene, 48% butyl acrylate and 2% acrylic acid by mass percentage.
[0045] The manufacturing method of the above-mentioned aqueous adhesive was as follows: 50 parts by mass of lithium polyacrylate was added to 550 parts by mass of deionized water, the water was heated to 70°C and stirred, 100 parts by mass of polymerizable monomer (above-mentioned mixed monomer) was added, and 0.25 parts by mass of ammonium persulfate was further added and reacted for 6 hours. After completion of the reaction, the pH value was adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above-mentioned aqueous adhesive.
[0046] Example 2 The aqueous adhesive and its manufacturing method are different from Example 1 only in that the lithium polyacrylate is replaced with an equal mass of potassium poly(2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate) (weight average molecular weight is 10,000, purchased from Macklin). The other components, compounding ratios and manufacturing methods are all the same as those of Example 1.
[0047] Example 3 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the lithium polyacrylate was replaced with an equal mass of sodium polystyrene sulfonate (weight average molecular weight 10,000, purchased from Macklin). The other components, compounding ratios, and manufacturing methods were all the same as those of Example 1.
[0048] Example 4 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the lithium polyacrylate was replaced with an equal mass of lithium polyvinylbissulfonylimide (weight average molecular weight 10,000, purchased from Macklin). The other components, compounding ratios, and manufacturing method were all the same as those of Example 1.
[0049] Example 5 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the mass ratio of lithium polyacrylate to polymerizable monomer was 1:49. The other components, compounding ratios, and manufacturing method were all the same as those of Example 1.
[0050] Example 6 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the mass ratio of lithium polyacrylate to polymerizable monomer was 4:1. The other components, compounding ratios, and manufacturing method were all the same as those of Example 1.
[0051] Example 7 The only difference between the aqueous adhesive and its manufacturing method in Example 1 is that the molecular weight of the lithium polyacrylate was 100,000. The other components, compounding ratios, and manufacturing method were all the same as in Example 1.
[0052] Example 8 The only difference between the aqueous adhesive and its manufacturing method and Example 1 is that the molecular weight of the lithium polyacrylate was 1,000,000. The other components, compounding ratios, and manufacturing method were all the same as those of Example 1.
[0053] Example 9 The aqueous adhesive and its manufacturing method are different from Example 1 in that the mass ratio of lithium polyacrylate to polymerizable monomer is 1:1, and the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, containing 40% styrene, 52% butyl acrylate, and 8% acrylic acid in terms of mass percentage content. The other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0054] Example 10 The aqueous adhesive and its manufacturing method are different from Example 1 in that the mass ratio of lithium polyacrylate to polymerizable monomer is 1:9, and the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, containing 52% styrene, 43% butyl acrylate, and 5% acrylic acid in terms of mass percentage content. The other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0055] Example 11 The water-based adhesive and its manufacturing method are different from Example 1 in that the polymerizable monomer contains, by mass percentage, 35% styrene, 60% butyl acrylate, and 5% acrylic acid; the other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0056] Example 12 The water-based adhesive and its manufacturing method are different from Example 1 in that the polymerizable monomer contains, by mass percentage, 60% styrene, 35% butyl acrylate, and 5% acrylic acid; the other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0057] Comparative Example 1 An aqueous adhesive and a method for producing the same, the aqueous adhesive being a copolymer of polymerizable monomers (styrene, butyl acrylate, and acrylic acid), the polymerizable monomers comprising, by mass percentage, 50% styrene, 48% butyl acrylate, and 2% acrylic acid.
[0058] The manufacturing method of the above-mentioned aqueous adhesive was as follows: 50 parts by mass of a polymerizable monomer was added to 200 parts by mass of deionized water, and 0.25 parts by mass of ammonium persulfate was further added, and the reaction was carried out at 70°C for 6 hours. After the reaction was completed, the pH value was adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above-mentioned aqueous adhesive.
[0059] Comparative Example 2 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the polymerizable monomer is a mixed monomer of styrene and acrylic acid, containing 98% styrene and 2% acrylic acid by mass percentage; the other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0060] Comparative Example 3 The aqueous adhesive and its manufacturing method differ from Example 1 only in that the polymerizable monomer is a mixed monomer of butyl acrylate and acrylic acid, containing 98% butyl acrylate and 2% acrylic acid in terms of mass percentage content; the other components, mixing ratios, and manufacturing method are all the same as those of Example 1.
[0061] Comparative Example 4 An aqueous adhesive and a manufacturing method thereof, the aqueous adhesive is a copolymer formed by reacting lithium acrylate (LiAA) with a polymerizable monomer, the mass ratio of lithium acrylate to the polymerizable monomer is 1:2, and the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, containing 50% styrene, 48% butyl acrylate, and 2% acrylic acid by mass percentage.
[0062] The manufacturing method of the above-mentioned aqueous adhesive was as follows: 50 parts by weight of lithium acrylate and 100 parts by weight of polymerizable monomer were added to 550 parts by weight of deionized water, 0.75 parts by weight of ammonium persulfate was further added, and the reaction was carried out at 70°C for 6 hours. After the reaction was completed, the pH value was adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above-mentioned aqueous adhesive.
[0063] Comparative Example 5 An aqueous adhesive and a manufacturing method thereof, the aqueous adhesive being a mixture of lithium polyacrylate and a terpolymer of styrene-butyl acrylate-acrylic acid, the mass ratio of the lithium polyacrylate to the terpolymer being 1:2, and the polymerizable monomers of the terpolymer containing, by mass percentage, 50% styrene, 48% butyl acrylate, and 2% acrylic acid.
[0064] The preparation method of the above-mentioned aqueous adhesive was as follows: 100 parts by weight of the polymerizable monomer of the terpolymer was added to 500 parts by weight of deionized water, 0.25 parts by weight of ammonium persulfate was further added, and the mixture was reacted at 70°C for 6 hours. After the reaction was completed, the pH value was adjusted to 7.0 with a 10% lithium hydroxide solution, and then 50 parts by weight of lithium polyacrylate was added to the system, which was stirred at room temperature and mixed uniformly to obtain the above-mentioned aqueous adhesive.
[0065] Comparative Example 6 A commercially available SBR adhesive, a water-based adhesive.
[0066] Comparative Example 7 A water-based adhesive, which is commercially available LA132 adhesive.
[0067] Application Examples A battery electrode piece is a negative electrode piece including a current collector (Cu foil) and a coating layer disposed on the current collector, the material of the coating layer includes a negative electrode active material (silicone material SiO-450, BTR New Energy Materials Inc., silicon content 10%), a conductive agent (carbon black SP), an adhesive and a thickener (sodium carboxymethylcellulose CMC), and the adhesive is a water-based adhesive provided by Examples 1 to 12 and Comparative Examples 1 to 7, respectively.
[0068] The manufacturing method of the above negative electrode pieces was as follows: the negative electrode active material, conductive agent, adhesive and thickener were mixed in a mass ratio of 96.5:1.0:1.0:1.5, added to deionized water at a solid content of 40 wt %, thoroughly mixed and stirred to form a uniform negative electrode slurry, which was passed through a 100 mesh screen, applied to a negative electrode current collector Cu foil, dried, and roll pressed with a roller at a unit length load of 10×104 N / m to obtain a negative electrode piece.
[0069] A lithium ion battery comprising a positive electrode piece, a negative electrode piece, a separator and an electrolyte, the negative electrode piece being the above-mentioned negative electrode piece, and the preparation method thereof is as follows:
[0070] (1) Preparation of positive electrode pieces: The positive electrode active material (lithium iron phosphate material), conductive carbon black, and adhesive (PVDF) were mixed so that the mass ratio of the solid content was 96.5:2.0:2.5, and added to N-methylpyrrolidone (NMP) at a ratio of 50 wt% of the solid content of the system, thoroughly mixed and stirred to form a uniform positive electrode slurry, which was passed through a 100 mesh screen and then applied to a positive electrode current collector Al foil, further dried, and rolled with a roller at 10 × 10 4 A roll press was performed with a unit length load of N / m to obtain a positive electrode piece;
[0071] (2) Negative electrode piece: as above;
[0072] (3) Separator: PE porous polymer film (Shenzhen Xingyuan Material Technology Co., Ltd.) is used as the separator;
[0073] (4) Assembly of lithium-ion battery: The positive electrode piece, separator, and negative electrode piece are wound in that order to obtain a cell, which is then sealed with an aluminum plastic film, baked to remove moisture, and then an electrolyte is injected. The lithium-ion battery is obtained through processes such as vacuum sealing, leaving, chemical conversion, secondary sealing, and shaping.
[0074] Performance test: (1) Swelling performance The water-based adhesive to be measured was dropped into a clean mold to ensure a solids content of 4g ± 0.1g, then placed in a drying box and dried at 70°C for 12h, a 1cm x 1cm section was removed and then dried at 120°C for 2h and prepared for use; the prepared film was weighed and the mass M1 was recorded; about 5g of electrolyte was weighed and added to the glass bottle containing the film, the bottle was sealed so that the electrolyte was completely immersed in the film, and the film was placed in a water bath at 85°C for 24h. The film was removed from the glass bottle, the electrolyte on the film was wiped off with clean airlaid paper, the film was dried, and the mass of the swollen film was weighed and recorded as M2.
[0075] Swelling rate = 100% x (M2-M1) / M1.
[0076] (2) Adhesive performance The negative electrode piece was cut into a long piece measuring 20 cm x 2.5 cm, and the collector side was attached to a 1 mm thick steel plate with double-sided tape. Cellophane tape was attached to the coating side. The coating layer was then peeled off in a 180° direction at a speed of 100 mm / min using a tensile tester, and the peel stress was measured. The peel stress was used as the basis for judging the adhesive performance. The higher the peel stress, the better the adhesive strength.
[0077] (3) Battery cycle and rate performance The lithium ion battery produced above was charged to 4.2V at a constant current of 0.33C, further charged at a constant voltage until the cutoff current became 0.02C, discharged to 2.5V at 0.33C, left for 5 minutes, charged to 4.2V at a constant current of 0.33C, further charged at a constant voltage until the cutoff current became 0.02C, and discharged to 2.5V at 0.33C for initial adjustment.
[0078] At 25°C, the initially conditioned lithium ion battery was charged to 4.2 V at a constant current of 0.5 C, further charged at a constant voltage until the cutoff current became 0.02 C, left for 5 min, then discharged to 2.5 V at a constant current of 1 C, left for 5 min, and the discharge capacity of the first cycle was measured. After 100 charge / discharge cycles in this manner, the discharge capacity at the 100th cycle was measured, and the capacity retention at the 100th cycle was calculated using the following formula:
[0079] Capacity retention at 100 cycles (%) = 100% × discharge capacity at 100th cycle / discharge capacity at first cycle.
[0080] Rate performance: At 25°C, the lithium ion battery after initial adjustment was charged to 4.2V at a constant current of 0.5C, further charged at a constant voltage until the cutoff current was 0.02C, left for 5 minutes, then discharged to 2.5V at a constant current of 1C, left for 5 minutes, and the discharge capacity at 1C was measured. Next, it was charged to 4.2V at a constant current of 0.5C, further charged at a constant voltage until the cutoff current was 0.02C, left for 5 minutes, then discharged to 2.5V at a constant current of 3C, left for 5 minutes, and the discharge capacity at a 3C rate was measured.
[0081] 3C capacity retention rate (%) = 100% x 3C discharge capacity / 1C discharge capacity.
[0082] The results of the performance tests are shown in Tables 1 and 2.
[0083] [Table 1]
[0084] In Table 1, "--" indicates that the component is not included and the data is not available.
[0085] [Table 2]
[0086] As can be seen from the performance test data in Tables 1 and 2, compared with the commercially available SBR water-based adhesive (Comparative Example 6) and LA132 adhesive (Comparative Example 7), the present application has given the water-based adhesive suitable swelling properties through the design of the structural units of the polymer metal salt and polymerizable monomer and their synergy, and the swelling rate after leaving in the electrolyte at 85 ° C for 24 hours can be adjusted within the range of 10 to 100%, and it also has good adhesive performance and lithium ion conductivity. When used with the negative electrode piece, the peel stress is 15 to 30 N / m, and the adhesive strength is significantly improved compared with the commercially available water-based adhesive. It also has good lithium ion conductivity, rate performance and cycle performance. The capacity retention rate of the lithium ion battery containing it at room temperature for 100 cycles is 97.5 to 99%, and the 3C capacity retention rate is 94 to 96.3%, and the cycle performance and rate performance are obviously improved. At the same time, by adjusting the ratio of the polymer metal salt and the polymerizable monomer, and designing the compounding ratio of the acrylate monomer and the olefin monomer in the polymerizable monomer, it is possible to adjust and optimize the performance of the water-based adhesive.
[0087] The aqueous adhesive provided by the present application is a copolymer formed by the reaction of a polymer metal salt with a polymerizable monomer, the polymerizable monomer including an acrylate-based monomer and an olefin-based monomer. By designing the structural units in the copolymer, the aqueous adhesive has a good balance effect among adhesion performance, lithium ion conductivity and swelling properties, and the adhesive does not lose adhesion due to too high swelling degree or lose lithium ion conductivity due to too low swelling degree, and has excellent adhesion strength, adhesion stability and electrochemical performance at the same time. When the aqueous adhesive does not include a structural unit of a polymer metal salt (Comparative Example 1), the swelling rate in the electrolyte is too high, the adhesion strength and lithium ion conductivity are insufficient, and the cycle performance and rate performance of the battery are significantly reduced. When the polymerizable monomer does not include an acrylate-based monomer (Comparative Example 2), the adhesive performance of the aqueous adhesive is low, and the cycle performance and rate performance of the battery are reduced. When the polymerizable monomer does not include an olefin-based monomer (Comparative Example 3), the performance of the aqueous adhesive is reduced, the capacity retention rate of the lithium ion battery is reduced, and the cycle performance is relatively low. Furthermore, when the polymer metal salt and styrene-butyl acrylate-acrylic acid terpolymer were present in the adhesive in a blend form (Comparative Example 5), or when the metal salt containing a double bond was copolymerized with another polymerizable monomer (Comparative Example 4), a copolymer containing a specific repeating unit and segment structure could not be formed, and the adhesive strength of the aqueous adhesive decreased, resulting in poor battery cycle performance.
[0088] The applicant declares that the present application describes the water-based adhesive and its manufacturing method and application through the above examples, but the present application is not limited to the above examples, i.e. does not mean that the above examples must be relied upon to implement the present application. It will be obvious to those skilled in the art that any improvements to the present application, equivalent replacement of each raw material of the product of the present application, addition of auxiliary ingredients, selection of specific forms, etc., are all within the scope of the claims and disclosure of the present application.
Claims
1. A water-based adhesive comprising: A copolymer formed by a polymer metal salt and a polymerizable monomer, the polymerizable monomer includes a combination of an acrylate-based monomer and an olefin-based monomer, and the polymer metal salt is any one or a combination of at least two selected from a metal phosphate-based polymer, a metal carboxylate-based polymer, a metal sulfonate-based polymer, and a metal bissulfonylimide-based polymer. Water-based adhesive.
2. The polymeric metal salt comprises any one or a combination of at least two of a polymeric lithium salt, a polymeric sodium salt, a polymeric potassium salt, or a polymeric magnesium salt; The water-based adhesive of claim 1.
3. The metal phosphate polymer is any one or a combination of at least two selected from the group consisting of metal polyphosphate, 2-methyl-2-acrylic acid-2-hydroxyethyl ester metal phosphate polymer, bis(2-(methacryloyloxy)ethyl) metal phosphate polymer, 2-methacryloyloxyethyl metal phosphate polymer, and vinyl metal phosphate polymer.
3. The water-based adhesive of claim 1 or 2.
4. The carboxy metal salt-based polymer is any one or a combination of at least two selected from the group consisting of a metal methacrylate-based polymer, a metal acrylate-based polymer, a metal maleate-based polymer, a metal itaconate-based polymer, a metal triallyl citrate-based polymer, a metal carboxymethyl cellulose-based polymer, and a metal alginate-based polymer. The water-based adhesive according to any one of claims 1 to 3.
5. The sulfonic acid metal salt polymer is any one or a combination of at least two selected from styrene sulfonic acid metal salt polymers, vinyl sulfonic acid metal salt polymers, propenyl sulfonic acid metal salt polymers, methacrylic acid metal salt polymers, 4-vinylbenzenesulfinic acid metal salt polymers, allyl vinyl sulfonic acid metal salt polymers, 3-sulfopropyl methacrylic acid metal salt polymers, methacrylic acid 2-ethanesulfonate metal salt polymers, 2-acrylamido-2-methyl-1-propanesulfonic acid metal salt polymers, acrylic acid-2-acrylamido-2-methylpropanesulfonic acid metal salt polymers, and 3-allyloxy-2-hydroxy-1-propanesulfonic acid metal salt polymers; Preferably, the bissulfonylimide metal salt polymer is selected from vinyl bissulfonylimide metal salt polymers and / or styrene bissulfonylimide metal salt polymers. The water-based adhesive according to any one of claims 1 to 4.
6. The weight average molecular weight of the polymer metal salt is 1,000 to 10,000,000; Preferably, the mass of the polymer metal salt is 1 to 90%, more preferably 10 to 50%, when the total mass of the polymer metal salt and the polymerizable monomer is 100%. The water-based adhesive according to any one of claims 1 to 5.
7. The acrylate monomer is an alkyl acrylate and / or an alkyl methacrylate, Preferably, the acrylate monomer is any one or a combination of at least two of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, pentyl acrylate, pentyl methacrylate, hexyl acrylate, hexyl methacrylate, octyl acrylate, isooctyl acrylate, or octyl methacrylate; Preferably, the olefinic monomer comprises any one or a combination of at least two of styrene, C5 to C10 linear or branched chain olefins; Preferably, the mass ratio of the acrylate monomer to the olefin monomer is (0.5-2):1, more preferably (0.8-1.5):1; The water-based adhesive according to any one of claims 1 to 6.
8. The polymerizable monomer further comprises a functional monomer, Preferably, the functional monomer comprises acrylic acid and / or methacrylic acid; Preferably, the mass percentage content of the functional monomer in the polymerizable monomer is ≦10%; The water-based adhesive according to any one of claims 1 to 7.
9. A method for producing the water-based adhesive according to any one of claims 1 to 8, comprising the steps of: mixing a polymeric metal salt, a polymerizable monomer, an initiator and a solvent, and then reacting to obtain the water-based adhesive; Manufacturing method.
10. The initiator comprises a persulfate, preferably ammonium persulfate. The method of claim 9.
11. When the mass of the polymerizable monomer is taken as 100%, the mass of the initiator is 0.05 to 5%; Preferably, the solvent comprises water; Preferably, the temperature of the reaction is between 60 and 80° C. Preferably, the reaction time is 1 to 12 h, Preferably, the method further comprises a neutralization step after completion of the reaction. The method according to claim 9 or 10.
12. 9. The application of the water-based adhesive according to any one of claims 1 to 8 in battery materials.
13. A battery pole piece, A battery pole piece comprising the water-based adhesive of any one of claims 1 to 8.
14. The battery pole piece includes a current collector and a coating layer disposed on the current collector, and a material of the coating layer includes the aqueous adhesive according to any one of claims 1 to 8; Preferably, the battery piece is a negative battery piece.
14. The battery pole piece of claim 13.
15. 1. A lithium ion battery, A lithium ion battery comprising the water-based adhesive of any one of claims 1 to 8 and at least one of the battery pole pieces of claims 13 or 14.
Citation Information
Patent Citations
Preparation method of negative pole piece water-based binder
CN111057184A
Binding agent, electrochemical device and electronic equipment using same
CN113795526A
Production of chloroprene rubber
JP1999021317A
Aqueous emulsion for adhesive
JP2003193010A
Aqueous dispersion type locking agent composition
JP2003194032A